1979
DOI: 10.1021/bi00579a016
|View full text |Cite
|
Sign up to set email alerts
|

Partial structure of a membrane glycopeptide from virus-transformed hamster cells

Abstract: The predominant surface glycopeptide from a clone of baby hamster kidney cells transformed by Rous sarcoma virus (C13/B4), metabolically labeled with L-[14C]fucose, has been characterized for the first time. This glycopeptide represents 19% of the total radioactivity removed by trypsin from the cell surface of the transformed fibroblasts and is more abundant in the transformed cells than in the normal counterpart. Purification of the glycopeptide after digestion with Pronase was by successive chromatography on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…Analysis of fucosyl-glycopeptides by gel filtration as well as by HPIC and affinity chromatography on Concanavalin A-Sepharose indicated that the glycopeptides derived from the tumor-DNA-induced transfectants were enriched in sialic acid-containing, highly branched glycan structures. These results are in agreement with studies on virally-transformed cells (Warren et al, 1978;Glick, 1979). Our data suggest a close relationship between the presence of rus oncogenes in transfectants and the alteration in fucose-containing membrane glycopeptides.…”
Section: Dlscussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Analysis of fucosyl-glycopeptides by gel filtration as well as by HPIC and affinity chromatography on Concanavalin A-Sepharose indicated that the glycopeptides derived from the tumor-DNA-induced transfectants were enriched in sialic acid-containing, highly branched glycan structures. These results are in agreement with studies on virally-transformed cells (Warren et al, 1978;Glick, 1979). Our data suggest a close relationship between the presence of rus oncogenes in transfectants and the alteration in fucose-containing membrane glycopeptides.…”
Section: Dlscussionsupporting
confidence: 93%
“…The cause of this alteration is thought to reside in the more complex, branched carbohydrate structures, in many cases enriched in terminal sialic acid residues (Ogata et al, 1976;Santer and Glick, 1979;Takasaki et al, 1980;Dorland et al, 1981). The changes in membrane glycopeptides on tumor cells may reflect functional alterations of tumor cells, e.g.…”
Section: Dlscussionmentioning
confidence: 99%
“…of deglycosylated SAF-protein to find out whether the differences are solely due to the different content of carbohydrate. The carbohydrate content of the different species would be in agreement with two N-linked carbohydrate chains for the 26-kd species and one N-linked carbohydrate chain for the 24-kd fraction, assuming an average content of five Nacetyl glucosamine residues per N-linked carbohydrate of rodents amster) (Sauter and Glick, 1979). We could not detect galactosamine in SAF-protein samples suggesting that these proteins do not contain 0-linked sugars.…”
Section: Purification Proceduresmentioning
confidence: 78%
“…The glycopeptides in polyoma-transformed baby hamster kidney cells have unusually high molecular weights due to the presence of external sialic acid as well as galactose and GlcNAc (2). The predominant surface glycopeptide of baby hamster kidney cells transformed by Rous sarcoma virus was determined to be a triantennary, completely sialylated, complex glycopeptide containing a core region of Man, GlcNAc, and Fuc (3). Synthesis of these elongated branches is initiated by 6-N-acetylglucosaminyltransferase (GnT-V; EC 2.4.1.155), which catalyzes the formation of the (31-6 branch (4).…”
mentioning
confidence: 99%